Safepaws a thera-generative sanctuary for animal farewells, emphaty, and pet afterlife wellbeing support - Dy, Larissa Austine C.; Sicam, Olivia Alma (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The unique and multifaceted bond between humans and animals transcends conventional social dynamics, fostering deep connections marked by genuine emotions and unwavering love. As animals reach the end of their lives, guardians grapple with complex emotions, underscoring the profound value of the human-animal bond. However, the lack of space and acknowledgment for navigating the grief associated with a pet’s end-of-life highlights a significant gap. This discrepancy is further emphasized by the concept of disenfranchised grief, characterizing the loss of a pet as not adequately supported or validated by society. This design project examines how architecture can provide a sanctuary for animal farewells, empathy, and pet afterlife well-being support to answer the deficiency of spaces for grief on a pet’s loss. Specifically, it will look at ways space can be programmatically developed to uplift and acknowledge the human-animal bond, particularly in designing spaces that support pet bereavement through Thera-generative approaches. It argues that integrating concepts of thera-generative, inclusive, responsive, and restorative has the potential to provide pet owners a venue for fostering healing and positive well-being. This project, by developing architectural design solutions to address disenfranchised grief and the deficiency of spaces for grief during pet loss, provides insight into the rarely acknowledged impact on pet owners during a pet’s loss.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Human-animal relationships; Pet loss; Animal sanctuaries